1998
DOI: 10.1002/(sici)1098-2795(199811)51:3<281::aid-mrd7>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo survival of frozen‐thawed bovine oocytes after IVF, nuclear transfer, and parthenogenetic activation

Abstract: Cryopreservation of bovine oocytes would be beneficial both for nuclear transfer and for preservation efforts. The overall objective of this study was to evaluate the viability as well as the cryodamage to the nucleus vs. cytoplasm of bovine oocytes following freezing-thawing of oocytes at immature (GV) and matured (MII) stages using in vitro fertilization (IVF), parthenogenetic activation, or nuclear transfer assays. Oocytes were collected from slaughterhouse ovaries. Oocytes at the GV, MII, or MII but enucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 0 publications
2
23
1
2
Order By: Relevance
“…For long-term storage of genetic resources, the cryopreservation of eggs has been established as a useful technique for laboratory animals [2,3,12,15] and domestic animals [7,9,10]. For short-term preservation, such as during long-distance transport, eggs do not always need to be frozen.…”
supporting
confidence: 88%
“…For long-term storage of genetic resources, the cryopreservation of eggs has been established as a useful technique for laboratory animals [2,3,12,15] and domestic animals [7,9,10]. For short-term preservation, such as during long-distance transport, eggs do not always need to be frozen.…”
supporting
confidence: 88%
“…Nevertheless, as Vajta et al (2009) write, the survival of vitrified oocyte is determined by a number of factors and the effect on the overall spindle condition should not be overestimated when compiling the protocol. This fact is also supported by results from MII stage oocyte cryopreservation quite comparable to GV stage (in which the spindle is not yet assembled) oocyte cryopreservation results (Fuku et al 1992;Kubota et al 1998;Zhou et al 2010). Our data confirmed that because the survival rate and following development of fertilized oocytes in preheated vitrification solution were equal to results reached at room temperature conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreserved oocytes can, in theory, be used to produce offspring via assisted reproductive techniques such as in vitro embryo production (Fuku et al 1992, Vajta et al 1998 or oocyte transfer (Maclellan et al 2002), and can also serve as host cytoplasts for cloning by nuclear transfer (Kubota et al 1998, Dinnyes et al 2000, Atabay et al 2004. However, while offspring have been produced using frozen-thawed oocytes in various species (e.g.…”
Section: Introductionmentioning
confidence: 94%